Genetic and Morphological Effects of Lactobacillus Acidophillus on Some Virulence Factors of Proteus Mirabilis That Isolated From Diabetic Foot Ulcers - Aseel Hussein Jaber, Suaad A. Fazaa Almiyah (Pakistan Journal of Medical & Health Sciences, 2022)
The current study have been included 250 samples diabetic foot ulcer patients attending in Al-Diwaniyah Teaching Hospital and private clinics at a period of study from beginning October 2021 to February 2022, Isolates were identified by morphological form on blood agar and macConkey agar, traditional biochemical tests,then confirmed by Vitek 2 system and PCR was performed using a specific primer (16SrRNA) to identify the genus Proteus and distinguish it from the other Enterobacteria and bacteria. Has been studied of the morphological and genetic inhibitory effect of probiotics on p. mirabilis and the results showed that Lactobacillus filters were more effective in the inhibitory effect on p. isolates mirabilis. Molecular study demonstrated the effect of LAB on virulence factors through the disappearance of some bands during electrophoresis. The number of bundles in the molecular study of virulence factors (ureR, zapA, flaA, hmpA) decreased after treatment of Proteus terrestris with lactobacillus acidophillus. Keywords: Proteus mirabilis, diabetes foot ulcers, Probiotic. Research aims: We focus on knowing the phenotypic and genetic effect of probiotics on some virulence factors of Proteus mirabilis isolated from diabetic foot ulcers in Al-Diwaniyah Governorate.